Implementing a community garden in a socially vulnerable urban area of Brazil - Feyh, Michele Hartmann (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2022)
Community urban gardens are a type of urban agriculture. They provide spaces for social interaction and increase in life quality of maintainers and consumers. This study implements a community garden in Vila Buritis II, Planaltina, Brasília, Federal District, Brazil. The population of Planaltina has low purchasing power and high indices of social vulnerability. The implementation of the vegetable garden resulted from a partnership between agroecology students from the Federal Institute of Brasília, the local community, and the government. The work relied on donations, reuse of materials, and volunteer labor. Educational actions in the neighborhood approached the relationship between production in the garden and food choices, with a focus on healthy eating, consumption of fresh food, and reduction of industrialized items. The building of the vegetable garden converted an idle area, with a history of accumulating garbage and rubble, into a productive space for social coexistence and leisure. Twenty-seven edible species and an undefined number of ornamental plants were planted. Between 30 and 40 residents visit the space regularly and collect food for their daily meals. However, the maintenance and increase of garden productivity still need technical assistance and resources.